Influence of Stock on the Early Tree Growth, Yield and Fruit Quality Traits of Apricot (Prunus armeniaca L.) - Tomo Mılosevıc (Journal of Agricultural Sciences)
This experiment was conducted in Cacak region (Western Serbia) in 2008-2010 to determine the effects of Myrobalan rootstock (Prunus cerasifera Ehrh.) and Blackthorn interstock (P. spinosa L.) on the tree growth, productivity and fruit quality traits of five apricot cultivars (P. armeniaca L.) grown under dry, sandy-loam and acidic soil conditions. The orchard established in 2007 at a 5.5 m × 3 m planting distance. The results showed that apricots grafted on Myrobalan appears to induce higher tree growth, yield (YI), cumulative yield (CY) and fruit weight (FW) when compared with the Blackthorn. Blackthorn showed a tendency to reduce a high vigour of apricot trees on Myrobalan, YI and fruit size. This interstock induced higher soluble solids/titratable acidity ratio (SS/TA ratio or RI) than Myrobalan. These results confirms the better adaptation of Myrobalan rootstock to dry, sandyloam and acidic soil than Blackthorn interstock.